A NON-NEWTONIAN APPROACH IN DIFFERENTIAL GEOMETRY OF CURVES: MULTIPLICATIVE RECTIFYING CURVES - Aydin, Muhittin Evren; Has, Aykut; Yilmaz, Beyhan (Korean Mathematical Soc, 2024)
In this paper, we study the rectifying curves in multiplicative Euclidean space of dimension 3, i.e., those curves for which the position vector always lies in its rectifying plane. Since the definition of rectifying curve is affine and not metric, we are directly able to perform multiplicative differential-geometric concepts to investigate such curves. By several characterizations, we completely classify the multiplicative rectifying curves by means of the multiplicative spherical curves.
Keywords: Rectifying curve; spherical curve; multiplicative calculus; multiplicative Euclidean space